2020
DOI: 10.3390/ijerph17093307
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone Use and Postural Balance in Healthy Young Adults

Abstract: Maintaining an upright posture while talking or texting on the phone is a frequent dual-task demand. Using a within-subjects design, the aim of the present study was to assess the impact of a smartphone conversation or message texting on standing plantar pressure and postural balance performance in healthy young adults. Thirty-five subjects (mean age 21.37 ± 1.11 years) were included in this study. Simultaneous foot plantar pressure and stabilometric analysis were performed using the PoData system, under three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 39 publications
5
20
0
1
Order By: Relevance
“…We used tablet-based cognitive tasks in part because of the increasing role of devices in daily life. Indeed, other cognitive-motor dual-tasking studies have found that using mobile devices can impact postural control for both younger and older adults ( Cho et al, 2014 ; Nurwulan et al, 2015 ; Laatar et al, 2017 ; Bruyneel and Duclos, 2020 ; Hsiao et al, 2020 ; Onofrei et al, 2020 ). Future work with larger samples is needed to extend investigations into the specificity of cognitive-motor dual-task interference on balance to more realistic tasks people complete on mobile devices.…”
Section: Discussionmentioning
confidence: 99%
“…We used tablet-based cognitive tasks in part because of the increasing role of devices in daily life. Indeed, other cognitive-motor dual-tasking studies have found that using mobile devices can impact postural control for both younger and older adults ( Cho et al, 2014 ; Nurwulan et al, 2015 ; Laatar et al, 2017 ; Bruyneel and Duclos, 2020 ; Hsiao et al, 2020 ; Onofrei et al, 2020 ). Future work with larger samples is needed to extend investigations into the specificity of cognitive-motor dual-task interference on balance to more realistic tasks people complete on mobile devices.…”
Section: Discussionmentioning
confidence: 99%
“…Second, childbearing women were in relatively young age among both groups. Young people often have the ability to use smartphone to watch videos via QR code Table 2 Subjects' baseline characteristics stratified by interventions Table 3 Percentage of score increasement in the comprehension a and satisfaction b between study groups [21]. Third, pregnant women have to schedule prenatal visits every 2 weeks after their 28th week of gestation; therefore, they have oppurtunities to discuss with anesthesiologist in their routine visits in hospital.…”
Section: Sdm Model Is Appropriate To Pregnancy Womanmentioning
confidence: 99%
“…Akıllı telefon kullanımının ayakta dururken ve yürürken spinal duruş ve pelvik pozisyon üzerindeki etkisini araştıran yakın zamanlı bir çalışmada, akıllı telefon kullanımının sagital ve frontal omurga parametrelerinde lomber lordoz gibi önemli değişikliklere yol açtığı gösterilmiştir (28). Sağlıklı genç yetişkinlerde akıllı telefonla konuşmak ve mesajlaşmak postural stabiliteyi önemli ölçüde etkilemektedir (29). Başın uzun süre öne doğru eğilmesi, alt servikal vertebralarda servikal lordozun azalmasına ve üst torasik vertebralarda kifozun artmasına neden olabilir.…”
Section: Discussionunclassified